Droit d'auteur et logiciel - Buron, Denis (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1987)
Under the present Canadian Copyright Act, it appears that protection is granted to computer programs, or software, as well as to flowcharts and firmware, or chips, whithout any relevant distinction. But the real problem is one of evidence. As a matter of fact, no layman can be expected to appreciate correctly a reproduction of a substantial part of a program where even experts are facing a troublesome task. New rules of evidence should be contemplated, based on behavior, since it is easier for the defendant to show that he did exercise creativity than for the plaintif to sustain that his work has been copied. That is especially important, considering that copyright seems to be the only answer for such badly needed protection.